GALD: new diagnostic tip for early diagnosis - a case report and literature review - Zermano, Silvia; Novak, Alice; Vogrig, Emanuela; Parisi, Nadia; Driul, Lorenza (Frontiers in Reproductive Health, 2023)
Objective Gestational alloimmune liver disease is a rare and serious condition caused by a maternal-fetal alloimmune disorder. There are not many studies about the antenatal treatment (IVIG infusion) of affected fetuses as the diagnosis is generally made postnatally. The possibility of an early diagnosis by means of ultrasonography and a gynecologist's assesment can provide prompt treatment of this disease. Case report We report the case of 38-year-old pregnant woman referred to our centre in view of severe fetal hydrops seen by ultrasound at 31 weeks + 1 day gestation. A male infant was born and subsequently died after developing liver failure. Postmortem examination revealed the presence of diffuse hepatic fibrosis in the absence of hemosiderin deposits and no extrahepatic siderosis. Immunohistochemical analysis was also performed which showed diffuse hepatocyte positivity for the terminal complement complex (C5b-C9) confirming the suspicion of GALD. Methods A comprehensive literature search published from 2000 to 2022 was conducted on PubMed and Scopus. Paper selection was performed following the PRISMA guidelines. Fifteen retrospective studies were identified and selected. Results A total of 15 manuscripts describing 26 cases were finally included in our research. Twenty-two fetuses/newborns with suspected GALD were studied, of which 11 had a confirmed histopathological diagnosis of GALD. Prenatal diagnosis of gestational alloimmune liver disease is difficult because ultrasound findings may be absent or nonspecific. Only one case report described fetal hydrops similar to our clinical case. As highlighted by the current case, in fetuses presenting with hydrops, once the most common etiologies have been excluded, hepatobiliary complications and liver failure caused by GALD should be considered Conclusions Global knowledge of this disorder and its wide spectrum of presentations may help to increase the number of cases that are diagnosed early and accurately. The recurrence rate of an infant being affected with GALD in another pregnancy is more that 90%. Recurrence however can be prevented by treatment with IVIG during pregnancy. This highlights the importance of having obstetricians and pediatricians familiar with gestational alloimmune liver disease.